Exploring the Relationship Between Burnout and Job Satisfaction Among Clinical Nurses - Yu-Hsia Lee; Mei-Hsiang Lin (European Scientific Journal, ESJ, 2019)
Aim. The purpose of this study was to explore the associations between burnout and job satisfaction among clinical nurses. Methods: A cross-sectional survey of 295 nurses were recruited from a medical center in Taiwan. Surveys were conducted using a demographic questionnaire, a Job Satisfaction Scale, and a Job Burnout Inventory. Results: The results were as follows: (1) both of the “personal burnout” and “external satisfaction” had the highest mean subscale score; (2) there were significant differences in the “work-related burnout” and the “overall burnout” related to those having children among the participating nurses (t=2.13, 2.10 p < .05); (3) there was a statistically significant relationship between the burnout, and the job satisfaction; (4) “personal burnout”, “work-related burnout”, and the “overcommitment to work” were related to the “inner satisfaction” and the “external satisfaction” (p < .05). Conclusion: This study’s findings may well provide guidance for the decision-making, and evidence for the need to improve job satisfaction in order to reduce burnout that may encourage nursing staff to retain their present jobs and improve the quality of care provided.